Matchmakers and trustbusters. (Economist, 2005)
The setting of prices in two-sided businesses intrigues economists and incites regulators. Such matchmaking businesses include singles bars matching the lovelorn of both male and females; television channels courting viewers and advertisers; personal computer operating systems attracting both software designers and software users; and payment cards that recruit both banks and retailers. Companies in these markets adopt different strategies to overcome the same intrinsic problems: they want to get both sides on board, keep them happy, and encourage them to take advantage of each other.